Preserving Literacy Instead of Strenghtening Media Literacy? - Smiljanić, Damir (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2024)
In today’s philosophical and scientific discourse on media, the concept of media literacy is increasingly mentioned. That term implies the art of effective use of new electronic media, which should also include a critical attitude towards them. ‘Media literacy’ thus becomes the fight slogan of a new critical thinking in the humanities. However, a closer examination of that term shows that it has its weaknesses: either it is tautologically conceived or the domain of its meaning is extended too much. The author starts from the position that the phenomenon of literacy is already elementary enough to be the subject of research in media philosophy and media science, because (extended) media literacy is also based on it. The starting point of a truly critical reflection on the media in today’s conditions should be the consideration of the reasons for the crisis of elementary (language) literacy. In support of his thesis, the author considers four aspects of that crisis – primacy of tactility, lack of attention, declining level of language culture and undifferentiated expression – and formulates the preservation of literacy in the sense of knowledge of language and the art of individual expression as a future task of philosophy and humanities.
Keywords: Keywords: media literacy, literacy crisis, tactility, attention, language culture, expression